(untitled) (European Journal of Economics, Finance and Business Development, 2025)
This article examines the analytical aspects of accounting in modern economic conditions. It explores the theoretical principles of accounting, its role in the financial management of enterprises, and development prospects. The study also includes an analysis of practical applications aimed at improving the efficiency of analytical accounting.